INFLUENCE OF DISTRACTIONS ON AUDIO AND VISUAL REACTION TIME IN YOUNG HEALTHY INDIVIDUAL OF 19-26 YEARS - Mahesh Makda, Meet; Gotmare, Neha; Deshpande, Mangala (International Journal of Clinical and Biomedical Research, 2017)
Background: Reaction Time is a measure of function of sensori-motor co-ordination and it is one of the valid and reliable tools for assessing cognitive functions. Purpose: The purpose of this study was to determine the influence of distractions on auditory and visual reaction time. Methodology: Testing was performed using a reaction time programmer developed with the help of JavaScript. 50 healthy participants (47 girls and 3 boys) aged between 19-26 years were exposed to different distractions (conversation, slow music, fast music and texting) in both ART and VRT tests. Results and Conclusion: Both auditory and visual reaction time with each distraction was found longer than normal. Auditory reaction time was maximally affected by conversation (f-value 8.27 and p-value). Key words: Auditory reaction time; Visual reaction time; Distractions; Sensori-motor co-ordination.